BS EN IEC 62841-3-3 AMDAA. Electric motor-operated hand-held tools, transportable tools and lawn and garden machinery. Safety. Part 3-3. Particular requirements for transportable planers and thicknessers (18th February 2022) - British Standards Institution,
No abstract available